Jejunal perforation secondary to migrated biliary stent. Issue 3 (15th March 2021) - Tabone, Renee; Yuide, Peter; Burstow, Matthew
Abstract: An 80-year-old female presented with acute left-sided abdominal pain. Cross-sectional imaging demonstrated a contained perforation around a migrated biliary stent within a large incisional hernia. Significant surgical background included an open cholecystectomy complicated by bile leak and insertion of a biliary stent 2.5 years prior. The stent had migrated at the time of attempted retrieval 10 weeks post-insertion. A decision was made to pursue conservative management after which time she remained asymptomatic until her acute presentation. Emergency laparotomy, adhesiolysis, stent removal, small bowel resection and abdominal wall closure were successfully performed in this case. In the setting of the biliary stent migration, it is important to consider individual patient's risk factors for acute perforation, such as intra-abdominal adhesions or diverticular disease, when deliberating conservative management versus elective surgical intervention for stent retrieval.